Effects of hot-drawing and annealing on the morphology and mechanical properties of biodegradable polyester monofilament fibers - J. Siripitayananon (2018)
Co/terpolymers of L-lactide (LL), ε-caprolactone (CL) and glycolide (G) are biodegradable in the human body and, as such, have considerable potential for use in biomedical applications such as absorbable surgical sutures, nerve guides, bone fixation devices and drug delivery systems. This study focuses its attention on their potential as monofilament fibers for absorbable suture applications. Random co/terpolymers with different compositions of LL, CL and G were synthesized via bulk ring-opening polymerization. The polymers obtained were melt spun at slow speeds into ice-cooled water to produce as-spun monofilament fibers with as little molecular orientation and crystallinity as possible. Combinations of off-line hot-drawing and annealing steps under controlled conditions of draw rate, draw ratio, temperature and time were then employed in order to develop the fiber's oriented semi-crystalline morphology. The mechanical properties of the fibers were tested after each processing step and compared. The tensile test results showed that the tensile strength was strongly dependent on the draw ratio. A high draw ratio was obtained by multiple off-line hot-drawings with intermediate annealing. The first hot-drawing step dramatically enhanced the mechanical properties relative to those of the weak, highly extensible as-spun fiber. Subsequent annealing at a suitable temperature and for an appropriate length of time increased fiber flexibility as a result of molecular relaxation. Additional hot-drawing steps, again under precise temperature-time conditions, increased the total draw ratio and further enhanced the fiber's mechanical strength. © Carl Hanser Verlag, Munich.